First reported case of Pascalia glauca poisoning in a pediatric patient: a case report - Rodríguez-Guerrero, Andrea Milena; Galán, Tania; Rodríguez-Guerrero, Marjorie; Patiño-Rocha, César; Vasconez-Gonzalez, Jorge; Ortiz-Prado, Esteban (Frontiers in Medicine, 2025)
BackgroundPascalia glauca is a toxic plant species predominant in South America, known to cause severe liver and kidney damage, and even death, in animal studies. Its toxicity is attributed to carboxyatractyloside, a compound that inhibits the transport of adenosine triphosphate (ATP) into the mitochondria, leading to cellular dysfunction. To date, no cases of human poisoning have been reported.Case reportWe present the case of a 6-year-old male who developed tonic-clonic seizures, altered consciousness, vomiting, and a Glasgow Coma Scale score below 8 after ingesting Pascalia glauca. A cranial CT scan revealed small intraparenchymal petechial hemorrhages in the biparietal and frontal regions. The patient was started on anticonvulsant and neuroprotective treatment with levetiracetam. Laboratory findings showed markedly elevated transaminases and coagulopathy, which did not improve with vitamin K administration, leading to a diagnosis of acute liver failure. The patient was treated with rifaximin, N-acetylcysteine, and lactulose, showing progressive improvement in liver function. After 27 days in the pediatric intensive care unit (ICU), he was transferred to the general ward hemodynamically stable but with persistent neurological impairment, unable to speak or respond to stimuli.ConclusionThis first reported case of human poisoning by Pascalia glauca highlights the plant’s potential neurotoxic and hepatotoxic effects in humans. The absence of prior human cases poses challenges in management and prognosis, emphasizing the need for increased awareness among healthcare professionals and further research on its toxicological impact.